Tensile Properties of Polypropylene Composites Reinforced with Alumina Nanoparticles and Short Carbon Fibers - João Lucas A.N.G. Ferreira; Marisa Cristina G. Rocha (Materials Research, 2023)
The good properties and high productivity obtained through injection molding have enabled the use of composites reinforced with short carbon fibers for the production of automobile components. Their low strength and stiffness, however, have limited the use of these materials in some applications. The incorporation of inorganic nanoparticles such as alumina (Al2O3) is a proposed solution to this problem. There is evidence that nanoparticles promote better interfacial interaction between the polymer and short carbon fibers, improving the mechanical performance of composites. The aim of this work was to develop polypropylene (PP) composites reinforced with alumina nanoparticles and short carbon fibers for the automotive industry. The composites were processed in a twin-screw extruder. The response surface methodology was used to define the content of nanoparticles in the composites and to evaluate the effect of the incorporation of the alumina and polypropylene-grafted maleic anhydride (PP-g-MA) on the properties obtained. The hybrid composite that showed the best tensile properties was used as a matrix for reinforcement with different levels of short carbon fiber. The tensile properties were determined by the standard techniques. The results showed that the materials obtained can be used in applications that require low density along with high productivity, rigidity and resistance.